Psych yourself rich : get the mindset and discipline you need to build your financial life - Torabi, Farnoosh (FT Press, 2011)
Examines the psychological aspects of dealing with financial issues and presents advice on establishing financial safeguards and goals and setting up a plan that will create financial security for the future